Pengaruh Perbandingan Eceng Gondok Dengan Air Terhadap Penyisihan COD Dan Padatan Pada Produksi Biohidrogen Secara Fermentasi Anaerob Batch Tahap Asidogenesis - Muria, Sri Rezeki; Fikri, Fikri; Ahmad, Adrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
In the last few years many researchers who made the breakthrough to create new and renewable energy. Sources of raw materials are often used are from organic waste, one of which is waste water hyacinth. Water hyacinth has a hemicellulose content that has the potential to be used as feedstock for the production of biohidrogen. Biohidrogen can be generated from the metabolism of anaerobic bacteria by fermentation. The purpose of this research is to produce biohidrogen with anaerobic batch fermentation process and determine the efficiency of COD and solids content. This study uses a bioreactor with a capacity of 15 L and variations substrate ratio is 1: 2, 1: 3, 1: 4 and 1: 5 at pH 6. The process of fermentation in this study lasted for 18 days. The parameters observed during the process that the efficiency of COD and solids removal efficiency which includes TS, TSS, TVS, and VSS. Results of the study showed that most COD removal efficiency was obtained at a ratio of substrate 1: 2 ie 76.32%, while for most solids removal efficiency is the ratio of 1: 2 to the value TS of 62.10%, amounting to 76.28% TSS, TVS VSS amounted to 54.71% and amounted to 80.62%. The products produced at the largest biohidrogen 1: 2 ratio of 3108.9 ml with biohidrogen content of 3.45%.Keywords : allowance solids, anaerobic , batch , biohydrogen , COD , water hyacinth